1998
DOI: 10.1002/j.2161-007x.1998.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Circle: An Alternative Path to Alcoholism Recovery

Abstract: Recovery from alcoholism has typically involved the program of Alcoholics Anonymous (AA). However, the values espoused by AA, especially those related to spirituality, can be in conflict with the values of traditional Native Americans. This article discusses healing methods founded in the traditions of Native American culture in general and the Oglala Lakota (also called Oglala Sioux) nation specifically. An understanding of these methods gives non‐Native American counselors additional tools for guiding Native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Most importantly, the women and staff interviewed see the group as being grounded in a distinctly socio-cultural context belonging to the women themselves. This is similar to group approaches used with indigenous individuals in residential rehabilitation in Australia (Berry, 2013;Chenhall, 2007) or in healing circles or sweat lodges in North America (Garrett et al, 2011;Stevenson, 1999;Vick et al, 1998). In the present study, this mixture of approaches appears to have enabled opportunities for learning in the group to be extended to cultural concepts, health facts, behaviour change, and getting earlier help for participants (e.g.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Most importantly, the women and staff interviewed see the group as being grounded in a distinctly socio-cultural context belonging to the women themselves. This is similar to group approaches used with indigenous individuals in residential rehabilitation in Australia (Berry, 2013;Chenhall, 2007) or in healing circles or sweat lodges in North America (Garrett et al, 2011;Stevenson, 1999;Vick et al, 1998). In the present study, this mixture of approaches appears to have enabled opportunities for learning in the group to be extended to cultural concepts, health facts, behaviour change, and getting earlier help for participants (e.g.…”
Section: Discussionsupporting
confidence: 64%
“…Access to social support is a strong determinant of good health (Richmond, Ross, & Egeland, 2007), and the unique value of indigenous-specific group support for individuals to address substance misuse and related harms has been described (Evans, Achara-Abrahams, Lamb, & White, 2012). Similar to other initiatives for indigenous individuals with SUDs (Chenhall, 2007;Stevenson, 1999;Vick et al, 1998), the women's group of this study draws on Aboriginal culture and storytelling to bring about positive change. However, few programs that are embedded in a socio-cultural approach have been systematically evaluated (McCalman et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Along these lines, Atkinson, Jennings, and Liongson (1990) found that Native American college students who anticipated lack of cultural responsiveness were more likely to avoid or decline the use of counseling services when needed. When it comes to enhancing the counselor's level of cultural responsiveness, scholars tend to agree on the importance of factors, including familiarity with Native American values (Baruth & Manning, 2003;Garrett, 2003), the provision of client-centered qualities (i.e., genuineness, positive regard, and empathy; Dillard & Manson, 2000;Garrett, 2003), and the flexible application of traditional counseling approaches (Trimble, Fleming, Beauvais, & Jumper-Thurman, 1996;Vick, Smith, & Herrera, 1998). However, when it comes to adopting an effective counselor role, scholars alternately recommend a directive role (Axelson, 1999;Trimble & LaFromboise, 1985), a nondirective role (Tanaka-Matsumi & Higginbotham, 1996;Wise & Miller, 1983), and the flexible application of a variety of roles (Atkinson, Morten, & Sue, 1997;Bland & Kraft, 1998;Carter, 1995;Steenbarger, 1993).…”
mentioning
confidence: 98%
“…Elders taught the up and coming generations through stories (Johnston, 1995, p. xiii), observation, participation, practice (Hains, 2001, p. 10) and role modelling (Hart, 1996, p. 64). Spirituality encompassed every part o f life for First Nations people (Vick, Smith, & Herrera, 1998), whether it was through dreams, ceremonies, or a prayer after a successful hunt, elders were there to impart their spiritual knowledge (Battiste & Barman, 1995, pp. 107-109), as spirituality was tantamount throughout the ages (Weenie, 1998, p. 59).…”
Section: First Nations Traditional Worldview Of Learningmentioning
confidence: 99%